Behavioural insights for improved uptake of agricultural sustainability assessment tools. Issue 2 (10th January 2022) - MacLeod, Catriona J.; Brandt, Angela J.; Collins, Kevin; Moller, Henrik; Manhire, Jon
Abstract: Changing human behaviour to enhance agricultural sustainability outcomes is an ongoing challenge that urgently needs addressing. It requires identifying the mechanisms for the successful uptake and application of tools and behavioural interventions to mitigate the detrimental impacts of farm activities on the environment. We combined a participatory action research and mixed‐methods approach (via online surveys, workshops, seminars, meetings and emails) to work with diverse stakeholders to understand their perspectives on the following: (a) sharing farm biodiversity data; (b) behavioural factors likely to influence farmer uptake and use of a farm‐level sustainability assessment tool developed for New Zealand farms; and (c) how to improve the tool. Respondents ( n  = 133) to an online survey were most willing to share data to gain advice on improving farm practices, but least willing when farmers were paid for the data, or companies used it to market products to farmers. Respondents were most comfortable with sharing data when an independent board decided the data‐use policies, or the contributor could change their sharing preferences and data were anonymised. Feedback on the tool prototypes was elicited via 27 events and more than 133 individual interactions. Of the 529 alignments between 255 discussion points and 14 behavioural factors, almost half were centred on the material context (e.g. infrastructures, technologies, time and schedules) but were often coupled with individual and social factors. Overall, a strong desire for a tool that empowers individual farmers to enhance their farm's biodiversity outcomes emerged, although, during the initial prototype tests, the tool's strengths were rarely acknowledged and concerns about weaknesses were more common. Ten strategies were identified for enhancing the tool. These aligned closely with three human‐thinking principles: four strategies focused on thinking automatically, three on thinking socially and seven on thinking using mental models. The system transformations required to implement such an integrated package of interventions to change behaviour at scale include a collective approach to developing a stronger evidence base for conservation actions, and behavioural interventions to enhance social and environmental capital in production landscapes. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.